Revealing the Identity, History and Nature Conservation Status of Royal Navy Vessel Steam Pinnace 744, in Lyness, Scapa Flow, Orkney IslesRevelando la identidad, historia y estado de conservación de la naturaleza del buque Pinaza a Vapor 744 de la Royal Navy, en Lyness, Scapa Flow, Islas Orcadas 揭示奥克尼群岛斯卡帕湾利内斯皇家海军蒸汽舰载艇 744 的身份、历史和自然保护状况 揭示奧克尼群島斯卡帕灣利內斯皇家海軍蒸汽艦載艇 744 的身份、歷史和自然保護狀況 - Porter JS; Anderson B; Fitzsimmons C; Heath KJ; Hives LL; Mair JM; Priest R; Robertson P; Sanderson WG (International Journal of Nautical Archaeology, 2023)
© 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.Presence of a steam pinnace at Lyness, Orkney Islands, was first documented in United Kingdom Hydrographic Office (UKHO) records by letter from a local scallop diver. Historic Environment Scotland (HES) tasked ORCA and Sula Diving Ltd to document this wreck during the Scapa Flow 2013 Marine Archaeology Survey. Side scan sonar and oral history provided initial clues to the identity. Reference to archival data and the Pinnace 199 renovation project (Portsmouth Historic Shipyard) enabled confirmation of its identity and understanding of how the vessel came to lie on the seabed off Rinnigal Pier. Photogrammetry revealed preservation status and during biological surveys two species of national conservation importance were recorded.